Following the financial crises in the tourism sector of selected countries : Analytical study - Hussain, Ali Jalal; Hiwa, Sara Hendren (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
The tourism sector is one of the fastest growing economic sectors in the world; thus tourism is becoming increasingly important to the countries of the world and the trend towards exploiting its tourism resources and to utilize its natural, historical, cultural and other tourism resources that attract different types of tourism (recreational, religious, medical, sports, or tourism etc.). This is due to the positive impact of tourism on the gross Domestic product through providing job opportunities, improving the balance of payments and hard currencies, in addition to attracting foreign and domestic investments. As a result, this research aims to analyze the effects of financial crises on the tourism sector (tourism demand and supply) in these selected countries (Turkey, Egypt and Iraq) using (analytical) methods, based on official data for different time periods representing crisis periods in those countries. The research concluded that the financial crisis has a negative effect on tourism sector in Turkey, Egypt and Iraq. The impact of internal crises was greater and stronger than the global financial crisis, Nevertheless, the research generally concluded a noticeable decrease in the number of tourists, tourism revenues, investments and provided tourism services. It recommends that the governments of the selected countries should direct towards diversifying tourism services, allocating a greater percentage to the tourism sector, raising its contribution from the total investment allocations